Respuesta :

Answer:

See below

Step-by-step explanation:

17.  17x + 3 x=4              18.  -2x + 1 / 3  x= -5

      17(4) + 3                          - [(2)(-5) + 1] / 3

      68 + 3                              - [-10 + 1] /3

       71                                       9/3  or 3

19.  2x - 33 x=9              20.  - 9x - 2  x=7

      (2)(9) - 33                         -(9)(7) - 2

       18 - 33                               -63 - 2

       - 15                                       -65

21.  7/3x - 9   x=3            22.  - [12x/5]   x= -1

      (7/3)(3) - 9                         - [(12)( -1)/5]

         7 - 9                                - [ -12/5 ]

         -2                                         2.4

23.  11x - 11   x = -11         24.  (2/9)x - (9/2)   x= 9

       - 121 - 11                           (2/9)(9) - (9/2)

         -132                                  2 - (9/2)  ( 2 can be shown as 4/2)

                                                      (4/2) - (9/2)

                                                          - 5/2  or   - 2.5

25.  f(x) = 0.12x + 4.52  x = 250     26.  f(x) = 0.18x + 3.12  x= 175

         = (0.12)(250) + 4.52                           = (0.18)(175) + 3.12

         = 30 + 4.52                                        = 31.50 + 3.12

         =  34.52                                             = 34.62

ACCESS MORE